Solving the ME/CFS criteria and name conundrum: the aftermath of IOM. Issue 2 (2nd April 2020) - Jason, Leonard A.; Johnson, Madeline
ABSTRACT: In 2015, the Institute of Medicine (IOM) proposed a new name and set of clinical criteria for what had previously been referred to as Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS). This committee recommended the adoption of the term systemic exertion intolerance disease (SEID) and clinical criteria that required specific symptoms such as post-exertional malaise and unrefreshing sleep. This article reviews efforts to evaluate the revised criteria as well as reactions to the new criteria and name. Since these recommendations have been made, the proposed name change has not been widely adopted by the scientific or patient community. Even though the IOM's proposed criteria were intended to be a clinical rather than a research case definition, over the past few years, an increasing number of studies have employed these criteria for research purposes. One unwitting consequence of the IOM criteria, which excludes few other illnesses, is the broadening of the number of individuals who are diagnosed and included in research studies. There is still a need to implement the IOM's recommendation to form a multidisciplinary committee to review research and policy changes following the release of the new criteria. We conclude by presenting a possible roadmap for overcoming barriers in order to make progress on developing a consensus for a name and criteria.